Contribution of Arm Explosive Power and Backstroke Flexibility to Plate Serving Ability in Field Tennis Games - Bismar, Ahmad Rum; Hakim, Hikmad; Nawir, Nukhrawi (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research aims to determine the contribution of arm explosive power and backstroke flexibility to plate serviceability in field tennis games. This research is a type of quantitative analysis research. The population and sample were tennis athletes from Polewali Mandar district, who were selected using a saturated sample, resulting in a sample of 20 people. The data analysis technique used was frequency using the SPSS Version 21.00 program. Based on the data analysis, it was obtained: 1) there is a significant contribution between the explosive power of the arm and the serviceability of the plate, as proven by the calculated r-value (ro) = 0.501 (p < 0.05). R square 0.251 This means that 25.1% of plate serving ability in tennis is influenced by arm explosive power. 2) There is a significant contribution between the flexibility of the backrest and the serviceability of the plate, as proven by the calculated r-value (ro) = 0.451 (p < 0.05). R square 0.204 This means that 20.4% of the ability to serve the plate in tennis is influenced by the flexibility of the backrest. 3) There is a significant relationship between the explosive power of the arm and the flexibility of the backkick on the serviceability of the plate, as proven by the calculated R value = 0.645 (P<0.05). R square value 0.417. This means that 41.7% of the ability to serve the plate in tennis is explained by the joint variables of arm explosive power and backbend flexibility.